Relações de gênero na história da ciência: a presença da mulher na física - SANTOS, Aline Lobato (2019)
In the development of this work, a deepening of the question of women in Physics was sought. This approach consists of two parts. In the first one, a historical analysis regarding gender and its implications in the development of Exact Sciences, especially Physics and women's lives. It also proposes a more realistic look at the fact that women are embedded in academic and professional circles. The second is a current approach, where questionnaires were applied to teachers of the Physics course, the same was available on the Google Drive platform. In this sense, the objective of the work is to know, through the questionnaires, the current reality of women who have opted in professional terms for the physics and to make a parallel with the evolution occurred in the mentalities of the feminine gender. Thus, it was possible to know in what way women are inserted in the courses of physics and in what way it is related in what concerns the relation of gender.